Regional Government According to the 1945 Constitution: Ideas Refinements and Law Reform - Muhammad Mutawalli Mukhlis; Maskun Maskun; Muhammad Saleh Tajuddin; Zulhilmi Paidi (Journal of Law and Legal Reform, 2024)
The concrete division of authority for government affairs between the center and the regions is still a matter of debate to this day, even though in principle the principle of broadest autonomy requires regional governments to carry out government affairs independently and freely. The principle of broadest autonomy in question is the independence of regional heads' powers. This research discusses things that hinder the role of regional governments in administering government according to the principle of broad autonomy and provides ideas for government models that are in accordance with the principles of concrete and pure autonomy in accordance with the mandate of the Indonesian constitution. This research aims to establish a regional government system that regulates the implementation of autonomous government in accordance with the principle of the widest possible autonomy as mandated by article 18 of the 1945 Constitution. This research is qualitative research, which is a normative legal study using a statutory, conceptual approach. and doctrinal. The material collection technique is through literature review, then the material is processed and analyzed in depth and presented in a descriptive analytical prescriptive manner. The results of this research found that there is a need for comprehensive management of regional affairs by regional heads as an embodiment of the principle of broadest autonomy.